Financial innovations and monetary reform how to get out of the debt trap - Serval, Jean-François; Tranié, Jean-Pascal (Future of Business and Finance, 2023)
Written by two leading experts on multinational accounting and billion-dollar international investment funds, this book provides a framework for a global reform of the world monetary system, and defines a decidedly new approach to dealing with public debt mortgage, an issue that we can see in many countries in Europe and around the world. The authors put forward a proposal for transforming sterile financial masses, which are withdrawn from the real economy as they no longer bear interest, into wealth. To facilitate this return to the real economy, the authors propose that a significant share of public debt be converted into net equities in the world of business and goods production in order to find new profitable investment projects. The idea is bold, and the authors strive to demonstrate its technical feasibility. They are convinced that this approach can accompany and enhance a movement that has already begun, namely the implementation of vast national and international investmentprograms in major infrastructures and research projects in innovative sectors.This work builds on the authors’ two previous books, which focus on the monetary system. The first, published in 2010 and including a foreword by former French Finance Minister Christine Lagarde, analyzes the new virtual dimension of money. The second, published in 2014, puts forward an innovative proposal for a new financial regulation aimed at more stable economies. This third book is intended for professionals in the financial industry, including decision makers at banks, accounting and private equity firms, as well as policymakers at central banks and government institutions involved in the implementation of financial and monetary reforms